Cloning and characterization of a gene (fadR) involved in regulation of fatty acid metabolism in Escherichia coli. - DiRusso, C C (1985)
The regulatory gene fadR has been previously characterized by classical genetic means as a diffusible protein which exerts negative control over fatty acid degradation and acetate metabolism. fadR has also been implicated in the regulation of unsaturated fatty acid biosynthesis. To facilitate the identification of the product of the fadR gene and to study the mechanism by which this multifunctional regulatory gene exerts its control, we cloned a segment of DNA containing the fadR gene in the phage vector lambda L47. Subsequent subcloning of a segment of the chromosomal DNA from the lambda fadR+ phage into various plasmid vectors resulted in the isolation of the fadR gene on a 1.3-kilobase-pair HindIII-EcoRV fragment. fadR strains harboring the cloned fadR+ gene showed inducible levels of fatty acid oxidation and crotonase (enoyl-coenzyme A-hydratase, fadB) activity. The cloned gene exerted transcriptional control over beta-galactosidase synthesis in an fadR strain that had a lambda phi (fad-lacZ+) operon fusion. An fadR mutation in fabA(Ts) strains prevents growth at permissive temperatures without unsaturated fatty acid supplementation (Nunn et al., J. Bacteriol. 154:554-560, 1983). Plasmids carrying the fadR+ gene suppress this unsaturated fatty acid auxotrophy in fadR fabA(Ts) strains at the permissive condition. Maxicell analysis identified a 29,000-dalton protein encoded by the 1.3-kilobase fragment which appeared to be associated with functional fadR gene activity.